The lateral parabrachial nucleus and central angiotensinergic mechanisms in the control of sodium intake induced by different stimuli - Roncari, Camila F. [UNESP]; David, Richard B. [UNESP]; De Paula, Patrícia M. [UNESP]; Colombari, Débora S.A. [UNESP]; De Luca, Laurival A. [UNESP]; Colombari, Eduardo [UNESP]; Menani, José V. [UNESP] (Elsevier, 2017)
Angiotensin II (ANG II) is a typical facilitatory stimulus for sodium appetite. Surprisingly, hyperosmolarity and central cholinergic stimulation, two classical antinatriorexigenic stimuli, also facilitate NaCl intake when they are combined with injections of the α2-adrenoceptor/imidazoline agonist moxonidine into the lateral parabrachial nucleus (LPBN). In the present study, we tested the relative importance of central angiotensinergic and cholinergic mechanisms for the control of water and NaCl intake by combining different dipsogenic or natriorexigenic stimuli with moxonidine injection into the LPBN. Adult male Holtzman rats (n = 9–10/group) with stainless steel cannulas implanted in the lateral ventricle and LPBN were used. Bilateral injections of moxonidine (0.5 nmol) into the LPBN increased water and 0.3 M NaCl intake in rats that received furosemide + captopril injected subcutaneously, ANG II (50 ng) or carbachol (cholinergic agonist, 4 nmol) injected intracerebroventricularly (icv) or 2 M NaCl infused intragastrically (2 ml/rat). Losartan (AT1 antagonist, 100 μg) or atropine (muscarinic antagonist, 20 nmol) injected icv abolished the effects on water and 0.3 M NaCl of moxonidine combined to either 2 M NaCl intragastrically or carbachol icv. However, atropine icv did not change 0.3 M NaCl intake produced by direct central action of ANG II like that induced by ANG II icv or furosemide + captopril combined with moxonidine into the LPBN. The results suggest that different stimuli, including hyperosmolarity and central cholinergic stimulation, share central angiotensinergic activation as a common mechanism to facilitate sodium intake, particularly when they are combined with deactivation of the LPBN inhibitory mechanisms.
Keywords: Angiotensin II; AT1 receptors; Cholinergic receptors; Osmoreceptor; Sodium appetite